The Effect of Trust and Knowledge Sharing on Team Effectiveness on a Virtual Team: A Case Study in Advanter (M) Sdn Bhd - From the Individual Perspective - Chan, Joon Moi (2010)
The objective of this study was twofold. First, the study was to examine the relationship between trust and team effectiveness in the virtual team environment. Second, it was to determine whether knowledge sharing plays a mediating role in this relationship. A total of 318 questionnaires were distributed to virtual team employees in Advanter(M) Sdn Bhd. However, only 167 questionnaires were returned and 106 were usable for analysis. Correlation analysis was used to test the inter-correlation between the variables. Correlation result shows that the three dimensions of trust, i.e personality based trust; cognitive base trust and institutional base trust, are correlated with team effectiveness. Hierarchical regression analyses were performed to tests the hypotheses of the study. The results indicated that team effectiveness is positively associated with trust and knowledge sharing and knowledge sharing was found to be a mediator in the relationship between trust and virtual team effectiveness.